Global stroke statistics 2023: Availability of reperfusion services around the world - Kim, Joosup; Olaiya, Muideen T; De Silva, Deidre A; Norrving, Bo; Bosch, Jackie; De Sousa, Diana A; Christensen, Hanne K; Ranta, Anna; Donnan, Geoffrey A; Feigin, Valery; Martins, Sheila; Schwamm, Lee H; et al. (International journal of stroke, 2024)
BACKGROUND: Disparities in the availability of reperfusion services for acute ischemic stroke are considerable globally and require urgent attention. Contemporary data on the availability of reperfusion services in different countries are used to provide the necessary evidence to prioritize where access to acute stroke treatment is needed. AIMS: To provide a snapshot of published literature on the provision of reperfusion services globally, including when facilitated by telemedicine or mobile stroke unit services. METHODS: We searched PubMed to identify original articles, published up to January 2023 for the most recent, representative, and relevant patient-level data for each country. Keywords included thrombolysis, endovascular thrombectomy and telemedicine. We also screened reference lists of review articles, citation history of articles, and the gray literature. The information is provided as a narrative summary. RESULTS: Of 11,222 potentially eligible articles retrieved, 148 were included for review following de-duplications and full-text review. Data were also obtained from national stroke clinical registry reports, Registry of Stroke Care Quality (RES-Q) and PRE-hospital Stroke Treatment Organization (PRESTO) repositories, and other national sources. Overall, we found evidence of the provision of intravenous thrombolysis services in 70 countries (63% high-income countries (HICs)) and endovascular thrombectomy services in 33 countries (68% HICs), corresponding to far less than half of the countries in the world. Recent data (from 2019 or later) were lacking for 35 of 67 countries with known year of data (52%). We found published data on 74 different stroke telemedicine programs (93% in HICs) and 14 active mobile stroke unit pre-hospital ambulance services (80% in HICs) around the world. CONCLUSION: Despite remarkable advancements in reperfusion therapies for stroke, it is evident from available patient-level data that their availability remains unevenly distributed globally. Contemporary published data on availability of reperfusion services remain scarce, even in HICs, thereby making it difficult to reliably ascertain current gaps in the provision of this vital acute stroke treatment around the world.
Keywords: worldwide; Ischemic Stroke; reperfuze; Thrombectomy; cévní mozková příhoda; trombektomie; Reperfusion; mobile stroke unit; Humans; telemedicine; lidé; sanitky; reperfusion; Ambulances; Stroke; ischemická cévní mozková příhoda